Bio-waste polymer hybrid as induced piezoelectric material with high energy harvesting efficiency. (February 2019) - Kumar, Chandan; Gaur, Anupama; Tiwari, Shivam; Biswas, Arpan; Rai, Sanjay Kumar; Maiti, Pralay
Abstract: Toxicity, biodegradability, biocompatibility and complex synthesis techniques are the major challenges in development for self-powered piezoelectric nanogenerators for biomedical applications. Here, we report a novel bio-waste hybrid with polymer for self-powered nanogenerator by using abundantly available natural self-aligned collagen fibrous fish scale as an efficient energy harvester. Fish scale induces the electroactive phase over its surface through synergism. Structure and morphology confirm the uniform distribution of scale particle in PVDF matrix and γ-phase formation in the presence of the filler. Energy harvesting performance of the bio-waste based hybrid device exhibit very voltage of 22 V and high energy density of 28.5 μW/cm 2, considerably higher value than the existing waste based device. Compressive stress by the human finger is sufficient to drive the bio-waste hybrid to generate energy along with other modes of naturally occurring vibration like twisting, bending, walking, foot tapping etc. Highlights: Induced piezoelectricity using bio-waste PVDF hybrid for energy generation High conversion efficiency has been reported using fish scale hybrid material Robust and durable device made of bio-waste fish scale hybrid with electroactive phase Different modes of stress can generate energy leading to versatile nature of device for biomedical applications